2022
DOI: 10.1002/glia.24160
|View full text |Cite
|
Sign up to set email alerts
|

The NLRP3 inflammasome modulates tau pathology and neurodegeneration in a tauopathy model

Abstract: An active role of neuroinflammation and the NLRP3 inflammasome in Alzheimer's disease and related tauopathies is increasingly identified, supporting NLRP3 as an interesting therapeutic target. However, its effect on tau‐associated neurodegeneration, a key‐process in tauopathies, remains unknown. While tau pathology and neurodegeneration are closely correlated, different tau forms may act as culprits in both characteristics and NLRP3‐dependent microglial processes may differently affect both processes, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…In a different study, it was discovered that tau hyperphosphorylation was decreased in the granular cell layer of the dentate gyrus, the CA1 cell body area, and the hippocampus [ 57 ]. Another study found similar results, with significantly less hippocampal atrophy in mice after tau [ 58 ]. Cleaved caspase-1 and ASC were found to be significantly more abundant in PD patients’ brains than in controls [ 59 ].…”
Section: Discussionsupporting
confidence: 56%
“…In a different study, it was discovered that tau hyperphosphorylation was decreased in the granular cell layer of the dentate gyrus, the CA1 cell body area, and the hippocampus [ 57 ]. Another study found similar results, with significantly less hippocampal atrophy in mice after tau [ 58 ]. Cleaved caspase-1 and ASC were found to be significantly more abundant in PD patients’ brains than in controls [ 59 ].…”
Section: Discussionsupporting
confidence: 56%
“…The levels of aggregated tau (Delta F%) were calculated using the ratios of the two emission signals (620 and 665 nm), according to the manufacturer formula. HTRF-tau aggregates values were previously shown to correlate with tau pathology in our tau model [ 50 ]. Measurements of Aβ42 and Aβ40 concentrations in brain were measured using the MSD VPLEX Plus Aβ Peptide Panel 1 (6E10) Kit (K15200G-1).…”
Section: Methodsmentioning
confidence: 93%
“…Tau aggregates concentrations in total brain homogenates were measured using the homogeneous time resolved fluorescence (HTRF) tau aggregation kit (6FTAUPEG; Cisbio, Perkin-Elmer, FR) according to previously validated protocols in our group, following the manufacturer protocol [ 50 ]. After incubation overnight of total brain homogenates of Tau transgenic mice with the anti-tau-d2 antibody and anti-tau-tb antibody at room temperature on a 384-well plate (Cisbio), the HTRF signals were measured with a TECAN Safire 2 microplate reader (Tecan Group Ltd., CH).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the role of NLRP3 inflammasome in tauopathy-induced neurodegeneration attracts extensive attention [24]. It was published that tauopathy (Tau hyperphosphorylation) and neurodegeneration (hippocampal atrophy) were decreased in the NLRP3deficient mice compared with wild type mice, implying its critical role [42]. However, how NLRP3 inflammasome modulates Tau phosphorylation is far from clear.…”
Section: Discussionmentioning
confidence: 99%